Effect of the 5E inquiry learning model with a SETS approach on junior high school students’ science learning outcomes and motivation - Ni Made Diantari Pratiyaksi; Ketut Suma; I Nyoman Jampel (Research and Social Study Institute, 2025)
This study aimed to examine the effect of the 5E Inquiry learning model integrated with the Science, Environment, Technology, and Society (SETS) approach on junior high school students’ science learning outcomes and learning motivation. A quantitative design with a pretest–posttest non-equivalent control group. The population consisted of all eighth-grade students, and the samples were selected through cluster random sampling. Learning outcomes data were collected using an objective test, while learning motivation data were obtained through a questionnaire. Data were analyzed using one-way MANCOVA after meeting the required assumptions. The results revealed a significant simultaneous difference in science learning outcomes and learning motivation between students taught using the 5E Inquiry model with the SETS approach and those taught through conventional instruction. Partially, the 5E Inquiry model with the SETS approach had a significant positive effect on both science learning outcomes and students’ learning motivation. In conclusion, the 5E Inquiry learning model integrated with the SETS approach is effective in improving the quality of science learning at the junior high school level.